Volatility interdependences in the Saudi stocks market - Yassin Ibrahim Eltahir; Osama Azmi Sallam; Hussien Omer Osman; Fethi Klabi (Universitas Islam Indonesia, 2019)
This study attempts to answer whether there is an interaction and volatility between the variances of the stock returns in the Saudi market. The sample represents daily stock prices of five sectors i.e. basic materials, banking, services, food, and transportation (SABIC, Al Rajhi, Etisalat, Almarai, and Al Bahri, respectively) from 2011 to 2016. The study applied the M-GARCH-DVEC methodology to estimate the variances of stock returns considering the interactions of returns. Findings/Originality: The results of the analysis show that there are fluctuations in the returns of stocks due to their interaction, but they are very slight as the results of the general trend of long-term variances. The study concludes that the variances between SABIC and Al Rajhi stocks are more stable compared to those of Etisalat, Almarai, and Al Bahri, which are relatively volatile. The results reveal that the variances in stock market returns are more likely to depend on internal factors.